Synthesis of Nanostructured Ferrites and Cation Distribution Studies by X-ray Magnetic Circular Dichroism, Mossbauer Spectroscopy, and X-ray Absorption Spectroscopy - Nandy, Subhajit; Latwal, Mamta; Pandey, Ganesh; Chae, Keun Hwa (Institute of Electrical and Electronics Engineers, 2022)
We present an extensive review of different techniques, such as x-ray magnetic circular dichroism, Mossbauer spectroscopy, and x-ray absorption spectroscopy, for determining the cation distribution in ferrites, and a comparison between these techniques is established. We describe the basic principles of these techniques to find the cation occupancies and highlight the important results obtained from these measurements on ferrite nanoparticles and thin films. Cation distribution, an important characteristic that controls the structural, electrical, and magnetic properties of ferrites, is strongly affected by the synthesis methods. Therefore, various synthesis techniques are reported for preparing ferrite nanoparticles and thin films. A summary correlating these techniques and the cation distribution in ferrite nanoparticles and thin films is presented.